Preffered cassava seeds must be readily available to farmers_Micheal Fieldman - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2017)
Dr. Micheal Fieldman explains the BASICS project approach to having 'preferred' Cassava seed readily available to farmers when they ask for it.